Financing, operationalizing, and implementing regional One Health coordination in Southeast Asia: Results of a regional workshop in Bangkok in 2023 - Lam, Steven; Sinh Dang-Xuan; Unger, Fred; Meeyam, T.; Phuc Pham-Duc; Wacharapluesadee, S.; Hung Nguyen-Viet (International Livestock Research Institute, 2024)
To inform regional commitments to working together through a One Health approach, we convened a 1.5-day workshop, inviting experts from government, national institutes, universities, and international organizations. Our study contributes action items that can support regional One Health efforts in Southeast Asia as well as efforts of other regions facing similar challenges relating to zoonoses, antimicrobial resistance and foodborne disease.